"How do you Criticize a Life Story?": Form, Trauma, and Memoir in Canada Reads - Brown, Taylor (Contemporary Kanata: Interdisciplinary Approaches To Canadian Studies, 2021)
“‘How do you Criticize a Life Story?’: Form, Trauma, and Memoir in Canada Reads 2020” investigates the practice of reading for empathy, as it pertains to memoir and trauma operating in the hypervisibility of the public sphere. The emotional connection between reader and author that memoir inspires is also encouraged on Canada Reads, the popular intersection of a literary contest and reality show. The panelists’ 2020 discussion of Jesse Thistle’s From the Ashes and Samra Habib’s We Have Always Been Here encouraged reading as a means of empathizing with the author’s experiences. As Danielle Fuller details, this is also how many viewers appraise the titles featured on Canada Reads, adopting a method of literary evaluation that is inherently personal. Memoir, given its connection to the real world and real people, becomes an excellent candidate for connecting with the reader. While Philippe Lejeune argues that memoir must be entirely non-fictional, G. Thomas Couser and Leigh Gilmore demonstrate that for a genre grappling with selective memory and trauma, this is impossible. As a result, memoir proves to be a genre that is both popular amongst readers and necessarily literary and inventive in its construction. The popularity of Canada Reads and memoir indicate that empathetic reading deserves a place in literary discourse, which in turn reimagines the Canadian literary canon and traditional methods of evaluation.